Analisis Penggunaan Gadget terhadap Tingkat Kebugaran Jasmani Siswa Putra Kelas 8 SMPN 1 Sukodono - Rama Sandi Firdaus; Andun Sudijandoko; Hijrin Fithroni; Ananda Perwira Bakti (Journal of Creative Student Research, 2025)
The use of social media today is not only among adults, in fact many children under 17 years old already have social media. Unfortunately, social media has many negative effects on children's lifestyles, if the child does not receive regular parenting from their parents regarding the use of social media. The aim of this research is to find out how the use of gadgets affects the physical fitness level of grade 8 male students at SMPN 1 Sukodono. The research method used is descriptive quantitative to analyze data by describing or illustrating the data. From the use of gadgets by 40 students, the results were 13% in the low category, 30% in the medium category, 38% in the high category, and 20% in the very high category. Meanwhile, the physical fitness results for grade 8 male students at SMPN 1 Sukodono were in the medium category with a score of 37,3. The results of the research on the intensity of gadget use of grade 8 male students at SMPN 1 Sukodono are in the high category with a percentage value of 38% and conversely, the physical fitness level of grade 8 male students at SMPN 1 Sukodono is dominant in the medium category with a VO²Max of 37.3.